EXTH-16. HUMAN PLACENTAL HEMATOPOIETIC STEM CELL DERIVED NATURAL KILLER CELLS FOR GLIOBLASTOMA IMMUNOTHERAPY. (11th November 2019) - He, Shuyang; Gleason, Joseph; Habboubi, Nassir; Hariri, Robert; Zhang, Xiaokui
Abstract: Taniraleucel (CYNK-001) is an allogeneic, off-the-shelf cell therapy enriched for CD56+/CD3- NK cells expanded from placental CD34+ cells. CYNK-001 exhibits in vitro cytotoxicity against various cancer cell types, including glioblastoma multiforme (GBM), and secretes cytokines during co-culture with cancer cells. To evaluate in vivo anti-GBM activity, safety and persistence of CYNK-001, we conducted two studies in the non-obese diabetic (NOD)-scid IL2Rgamma null (NSG) immune deficient mouse models. First, CYNK-001 in vivo anti-GBM activity was assessed in a U-87MG orthotopic NSG mouse model. Luciferase-expressing U-87MG cells were stereotactically injected into the cranium of NSG mice at Day 0. Repeated dosing of 0.5x10 6 CYNK-001 cells at Day 14 and Day 25 by intracranial (IC) injection showed a statistically significant reduction of Bioluminescence Imaging (BLI) compared to the PBS control. Furthermore, intravenous (IV) and intracerebroventricular (ICV) routes of administration were evaluated compared to IC. CYNK-001 administered with IC resulted in a greater reduction of BLI than IV and ICV. Second, a single-dose toxicity study was conducted in naïve NSG mice to assess the safety and persistence of CYNK-001 following an IC injection. IC administration of 1×10 6 CYNK-001 was well tolerated, and no adverse clinical symptoms were observed. Quantitative polymerase chain reaction (qPCR) analysis for the human telomerase reverse transcriptase (hTERT) gene revealed that CYNK-001 persisted in the brain up to seven days. Our studies demonstrated that CYNK-001with IC administration appears safe and well tolerated in naïve as well as U-87MG tumor bearing NSG mice. Furthermore, CYNK-001 anti-tumor activity was exhibited in a GBM orthotopic NSG mouse model. Taken together, our data support a safety and efficacy evaluation of CYNK-001 in patients with GBM. A Phase 1 study in adult patients with recurrent/refractory GBM is planned to start this year evaluating the safety and efficacy of CYNK-001 with both IV and IC administrations.